Cell-specific transcriptional control of the mouse DNA-binding protein mC/EBP. - Xanthopoulos, K G (1989)
The mRNA encoding the mouse homolog of C/EBP, a rat DNA-binding protein that participates in activating a number of genes in hepatocytes, is present in liver cells at a far higher concentration than in most other cells, including spleen, kidney, muscle, and the majority of the brain. However, fat cells and intestinal cells contain 25-50% as much mRNA as liver cells. "Run-on" experiments show that the basis for the restricted cellular distribution of the mouse C/EBP mRNA is transcriptional regulation of the gene. We also show that disruption of cell-cell contacts incident to liver cell dispersion results in a prompt and extensive reduction in mouse C/EBP transcription as we had earlier shown to be the case for a group of 10 genes transcribed in a hepatocyte-specific fashion. In contrast, breaking cell contacts and plating the hepatocytes in culture leads to a prolonged increase in transcription of the Jun-B gene that encodes a widely distributed transcription factor. These results illustrate that the regulation of expression of a mammalian regulatory protein with limited tissue distribution is controlled at the level of transcription and depends on cell contacts.